1999
DOI: 10.1177/104973159900900402
|View full text |Cite
|
Sign up to set email alerts
|

Validating School Social Work: An Evaluation of a Cognitive-Behavioral Approach to Reduce School Violence

Abstract: Objective: This study evaluated the effectiveness of anger control training with conduct-disordered male adolescents at a day treatment program. Method: A multiple baseline single-subject design across subjects was used to assess matched pairs of students (8 experimental and 8 control students). Combined visual analyses and group comparison methods were used in the assessment. Results: The experimental students significantly improved in their weekly self-reports of using better anger control and experiencing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 22 publications
2
4
0
2
Order By: Relevance
“…These results are consistent with Whitfield (1999) who found that at six-month follow-up participants maintained improvements in self-control after a cognitive behavioural anger control intervention. In contrast, parent ratings of behaviour returned to pre-intervention levels.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are consistent with Whitfield (1999) who found that at six-month follow-up participants maintained improvements in self-control after a cognitive behavioural anger control intervention. In contrast, parent ratings of behaviour returned to pre-intervention levels.…”
Section: Discussionsupporting
confidence: 90%
“…In relation to RQ2, it was found that improvements in self and teacher ratings were maintained at six-month follow-up according to teacher and self-report measures. These results are consistent with Whitfield (1999) who found that at six-month follow-up participants maintained improvements in self-control after a cognitive behavioural anger control intervention. In contrast, parent ratings of behaviour returned to pre-intervention levels.…”
Section: Discussionsupporting
confidence: 90%
“…Remaja yang berperilaku agresif seringkali osial. Bias inilah yang kemudian mendorong mereka untuk berperilaku agresif ketika menghadapi konflik atau kondisi yang tidak menyenangkan (Whitfield, 1999;Berkowitz, 2003).…”
unclassified
“…A second gap in the research concerns the paucity of cognitive-behavioral anger management programmes which include a follow-up assessment, as a means of examining whether the effects of the intervention are temporary or sustained (van de Wiel, Matthys, Cohen-Kettenis, & van Engeland, 2002). While some researchers question the maintenance effects of cognitive-behavioral group interventions (Humphrey & Brooks, 2006), others report that effects are sustained (Broota & Sehgal, 2004; Muris, Meesters, Vincken, & Eijkelenboom, 2005; Whitfield, 1999) or, indeed, enhanced (Hemphill & Littlefield, 2001; Martsch, 2005) when follow-up assessments are conducted.…”
mentioning
confidence: 99%